Treatment outcome in depressed alcoholics - Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Alcoholism and Substance-Abuse - Course and Outcome - Hesselbrock, V; Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Suicide attempts and alcoholism - Hesselbrock, M.; Hesselbrock, V.; Syzmanski, K.; Weidenman, M. (Journal of Studies on Alcohol, 1988)
This study examined the association among suicide attempts, parental alcoholism, psychopathology and drinking history in a sample of hospitalized alcoholics. Suicide attempters were found to have multiple psychiatric diagnoses (e.g., depression, antisocial personality disorder and substance abuse) and more severe psychiatric symptoms than nonattempters. Alcoholic suicide attempters also tended to have a parental history of alcoholism and began abusing alcohol at an early age. Alcohol abuse symptoms during the month before, and 6 month before, the current hospitalization were generally similar for suicide attempters and nonattempters. Clinical implications of the findings are discussed.
Keywords: adult; age; alcoholism; dept.swk; epidemiology; female; human; male; mental disease; normal human; oral drug administration; preliminary communication; psychological aspect; suicide attempt